Application Of Problem Solving Learning Model Through Lesson Study On Critical Thinking Ability Of Students At Yabt Manokwari Kristen High School - Astutik, Novita Santi; Widyaningsih, Sri Wahyu; Sinon, Iriwi L.S. (Al-Khazini: Jurnal Pendidikan Fisika, 2023)
This study aims to see the implementation of the problem solving learning model based on lesson study and to see the students' critical thinking skills and student responses after learning with the problem solving model. This research was conducted at the YABT Christian High School Manokwari in the 2021/2022 academic year. This research is a lesson study research with research subjects in class X IPA totaling 14 students. The research data collection technique used was a test in the form of critical thinking questions, non-test in the form of a response questionnaire to the learning model and activity observation sheets. The data analysis technique used is descriptive qualitative analysis, descriptive analysis of critical thinking, and questionnaire response analysis to the learning model using Rasch modeling. The research data were obtained from the results of observation sheets, critical thinking questions and questionnaire responses to the learning model. The results of the implementation of lesson study during the learning cycle I and cycle II showed that learning activities were well observed and showed good student responses, and increased critical thinking skills, seen from the results of tests and observations of observers. The critical thinking ability of students in solving problems is known through thinking analysis where the value of the 4 indicators is included in the sufficient criteria with an average value of 49.92. Then the results of the student response questionnaire in general indicate that in general students have a good response to learning.